Highly efficient solar steam generation of bilayered ultralight aerogels based on N-rich conjugated microporous polymers nanotubes. (5th March 2020) - Zhu, Zhaoqi; Mu, Peng; Fan, Yukang; Bai, Wei; Zhang, Zheng; Sun, Hanxue; Liang, Weidong; Li, An
Graphical abstract: N-rich conjugated microporous polymers nanotubes with high porosity, low thermal conductivity and superior mechanical strength was prepared for solar steam generation, which exhibits a high evaporation efficiency of 80% under 1 sun irradiation. Highlights: N-rich conjugated microporous polymers nanotubes was prepared for solar steam generation. It possesses high porosity, low thermal conductivity and superior mechanical strength. It exhibits a high evaporation efficiency of 80% under 1 sun irradiation. Abstract: Solar steam generation is one of the most promising and efficient methods to solve freshwater shortage and to treat the wastewater over the world. However, the preparation of the solar steam generator with simple preparation process, controlled porous structure, high mechanical strength and energy conversion efficiency is still a challenge. Here, we report a bilayered heterocyclic conjugated microporous polymers aerogels based solar receiver by combination of the one-pot Sonogashira–Hagihara reaction of 2-amino-3, 5-dibromopyridine and 1, 3, 5-triethynylbenzene and spraying the polypyrrole on the surface of the aerogels for the solar steam generation. The as-prepared solar steam generator shows nanotubular structure with high porosity (94%), excellent light absorption (ca. 94%), low thermal conductivity (0.031 W m −1 k −1 ), rapid water transport performance and superior mechanical strength (0.54 MPa under 75% of strain). Under 1 sun illumination, the conjugated microporous polymers aerogels based solar steam generator achieved a high energy conversion efficiency of 80%. This work may provide a simple and novel way to design and fabricate solar receiver with adjustable structure.